The Role of Gender Inclusivity in Promoting a Sustainable Economy: A Study on Women's Empowerment among MSMEs in Kutai Kartanegara Regency, East Kalimantan - Yahya Ayyashy Farhani; Handri Ramdhani; Maria Ariesta Utha; Kurniawati Kurniawati (Dinasti Publisher, 2025)
Gender inclusivity plays a crucial role in promoting sustainable economic development through women's empowerment in Micro, Small, and Medium Enterprises (MSMEs) in Kutai Kartanegara Regency, East Kalimantan, Indonesia. This study aims to analyze the challenges, opportunities, and impacts of women's empowerment in MSMEs. A qualitative research approach was employed, using purposive sampling of four MSME group leaders in Kutai Kartanegara. Data were collected through semi-structured in-depth interviews conducted online in July 2025 and analyzed using Braun and Clarke's (2019) thematic analysis. Women's empowerment through MSMEs provides significant multidimensional impacts. MSMEs have proven to be flexible environments for empowerment, characterized by empathetic, collaborative, and sustainability-oriented leadership. Despite challenges such as limited capital, small production scale, and gender inequality, women MSME actors develop adaptive strategies through product diversification, waste utilization, and business network development. These efforts result in improved family welfare, job creation, and contributions to sustainable economic growth. Women's empowerment through MSMEs is an effective strategy for sustainable socio-economic transformation, achieved through three pillars: building self-confidence, open communication, and empowering other women. The multidimensional impact encompasses economic, social, and environmental aspects, requiring comprehensive institutional support to make MSMEs the engine of sustainable inclusive economic growth.